PEMBINAAN MASYARAKAT TENTANG KOMERSIALISASI DAN STERILISASI INDUSTRI PADA PENGOLAHAN ABON SAPI - Yofitri Heny Wahyuli; Asmawati; Aryanisila; Holipah (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2023)
This community partnership service aims to increase community productivity and income by empowering the people's economy and assisting small and medium businesses with stimulant skills in the field of technology and hygienic management of the production of